A Novel Prognostic Biomarker of Luminal Breast Cancer: High CD39 Expression Is Related to Poor Survival - Ni, Xiaojian; Wan, Wenze; Ma, Jingjing; Liu, Xinyou; Zheng, Bohao; He, Zhixian; Yang, Weige; Huang, Lihong (Frontiers in Genetics, 2021)
Abstract Background: CD39 is one of the functional surface markers for T regulatory cells (Treg), the prognostic role and immune-related effects of CD39 in luminal BC patients has not been evaluated yet. The aim of the current study was to explore the association between CD39 expression in BC and clinic pathological characteristics and the prognosis of luminal BC patients using The Cancer Genome Atlas (TCGA)-BRCA level 3 data. Methods: Clinical information and RNA-sequencing (RNA-Seq) expression data were downloaded from TCGA. Patients were divided into a high or low CD39 expression group using the optimal cutoff value (4.46) identified from the receiver operating characteristic (ROC) curve analysis. The relationships between CD39 expression and clinic pathological features were evaluated by the corresponding statistical tests. Survival analyses were applied to evaluate the OS between the high and low CD39 expression groups in luminal BC. Furthermore, Gene Expression Omnibus (GEO) datasets were used for external data validation. Gene set enrichment analysis (GSEA) was also performed, and CIBEREORT was used to analyze the immune cell fractions. Results: Compared to normal breast tissues, CD39 was overexpressed in BC (P=0.0009). The multivariate analysis suggested that CD39 expression might be an independent prognostic factor for luminal BC patients, regardless of whether in training dataset (HR: 2.310, 95% CI: 1.151–4.637) or validation dataset (HR: 1.602, 95% CI: 1.009–2.543). GSEA suggested that CD39 might play an important role in luminal BC progression through immune regulation. Analysis of immune cell patterns revealed a higher proportion of CD8+T cells and M2 macrophages, suggesting that CD39 can promote tumor-associated macrophages (TAMs) towards M2 differentiation. Conclusion: This is the pilot study to demonstrate that CD39 expression correlates with the prognosis of luminal BC through TCGA database mining. Further studies are warranted further to elucidate this potential novel therapeutic strategy for BC.